Intrathecal Dexmedetomidine-Fentanyl Combination versus Fentanyl Alone as Adjuvant to Bupivacaine in Spinal Anesthesia: A Comparative Study at Haji Adam Malik General Hospital - Saputra, Firdaus; Hamdi, Tasrif; Irina, Rr Sinta (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Spinal anesthesia is a regional analgesia that blocks nerve cells in the subarachnoid space by local anesthetic drugs. Bupivacaine is the most common agent, however, the duration of analgesia is often short. However, this advantage is hampered by the limited duration of spinal anesthesia and the uncomfortable postoperative period when the effect wears off. To prolong the duration of analgesia, various drugs such as opioids and α2 adrenergic agonists can be used as adjuvants for intrathecal local anesthetics to improve the quality of spinal anesthesia. One of the most widely used opioids is fentanyl, while the α2 adrenergic agonist is dexmedetomidine.Objective: To analyze the difference in effectiveness of the combination of dexmedetomidine 5µg and fentanyl 25µg intrathecally with fentanyl 25µg as an adjuvant to bupivacaine in spinal anesthesia.Method: This study is a double-blind randomized clinical trial to assess the comparison of the combination of dexmedetomidine 5µg and fentanyl 25µg intrathecally with fentanyl 25µg as an adjuvant to bupivacaine on the onset of block, duration of action, and side effects in surgery with spinal anesthesia.Results: There were 32 samples with a distribution of 16 samples in each group. There was a significant difference in sensory and motor duration (p<0.001). The average sensory duration in the fentanyl group was 2 hours 45 minutes, and in dexmedetomidine + fentanyl, 4 hours 25 minutes. In comparison, the motor duration in the fentanyl group was 2 hours 30 minutes, and in the dexmedetomidine + fentanyl was 4 hours 2 minutes.Conclusion: There is a comparison of the effectiveness of administering dexmedetomidine 5 mcg + fentanyl 25 mcg intrathecally and fentanyl 25 mcg intrathecally as an adjuvant to 0.5% bupivacaine in the spinal, where the dexmedetomidine group had a longer duration of anesthesia than the fentanyl group.